Medullary unidentified bright objects in Neurofibromatosis type 1: a case series - Alessandra D'Amico; Federica Mazio; Lorenzo Ugga; Renato Cuocolo; Mario Cirillo; Claudia Santoro; Silverio Perrotta; Daniela Melis; Arturo Brunetti (BMC, 2018)
Abstract Background In Neurofibromatosis type 1, cerebral Unidentified Bright Objects are a well-known benign entity that has been extensively reported in the literature. In our case series, we wish to focus on a further possible location of such lesions, the spinal cord, which we have defined as medullary Unidentified Bright Objects. These have been, to our knowledge, scarcely described in previous works. Case presentation We report the cases of 7 patients with medullary Unidentified Bright Objects in Neurofibromatosis type 1 that we have followed for up to 9 years in our Regional Referral Center for Neurofibromatosis. In all of our patients, these lesions were completely asymptomatic and reported on Magnetic Resonance exams the patients underwent for other clinical indications. Conclusions The aim of our work is to increase awareness of the possibility of medullary Unidentified Bright Objects in Neurofibromatosis type 1 patients, which can simulate neoplastic lesions, suggesting a more conservative approach in these cases.